Partial Sheehans Syndrome with Primary Hypothyroidism- A Delayed Diagnosis - Khan, Nora Anwar; Ekram, Rezaul; Mallick, Pronob Kumar; Islam, Mohammad Rafiqul; Amin, Md Robed (Journal of Medicine, 2017)
In Sheehan;s syndrome hypopituitarism is caused by the ischemic damage to the pituitary following postpartum hemorrhage and vascular collapse. In Sheehan;s syndrome secondary hypothyroidism occurs. We report here a case of partial Sheehans syndrome with primary hypothyroidism with high anti thyroid antibody titre which is an uncommon association. J MEDICINE July 2017; 18 (2) : 115-118